Uso de applets do GeoGebra na matemática: uma sequência didática de análise combinatória para o ensino médio - Abreu, Luís Lindemberg Souza (2024)
In Mathematics teaching, the search for innovative methodologies has intensified, especially to overcome challenges related to the understanding of abstract concepts and problem-solving. One of these approaches is the didactic sequence, which highlights the student’s leading role in the learning process. This study presents the development of a didactic sequence for teaching Combinatorial Analysis, using GeoGebra software as a pedagogical resource. The proposal aimed to integrate practical activities, such as visual exploration of combinations and interactive simulations, with the resolution of contextualized problems, promoting a more concrete and dynamic understanding of the concepts. The results indicated that the use of GeoGebra has the potential to significantly promote learning, especially through proposals for applets developed for teaching combinatorics. These tools assist in the exploration of concepts such as modifications, permutations and combinatorial patterns, in addition to favoring the resolution of problems applied to real scenarios. The four applets proposed in this work offer innovative and interactive resources for teaching Mathematics, contributing to the improvement of educational practices and providing support for the adoption of more effective and contextualized strategies in the classroom